PENGARUH PENGGUNAAN LAGU-LAGU DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Fransisca Regy Reviana (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2023)
AbstractEducation plays an important role in shaping the character of individuals, which in turn influences human behavior. In the context of education in elementary schools, the use of songs can be an effective way to shape the character of students. However, the influence of the use of songs in the formation of character of students in elementary schools has not been fully understood and studied scientifically. Therefore, this study aims to examine the influence of the use of songs in the formation of character of students in elementary schools. In this study, a qualitative approach was used with questionnaires as a tool to collect data from 156 teachers teaching in elementary schools in Indonesia. Data was obtained through filling out a questionnaire by the teacher consisting of 15 questions related to the use of songs in character building. The results showed that the use of songs in the formation of student character in elementary schools had a positive impact on student character, such as increasing honesty, tolerance, and togetherness. In this article, we will discuss the concept of character education, the role of songs as learning tools, and the effects of their use in shaping student character. Keywords: Influence, Songs, Character Building, Learners, Elementary School